2019
DOI: 10.1186/s40814-019-0526-2
|View full text |Cite
|
Sign up to set email alerts
|

An iterative design process to develop a randomized feasibility study and inform recruitment of minority women after stillbirth

Abstract: BackgroundYearly, approximately 25,000 US women experience stillbirth and African American women have a 2.2 fold increased risk of stillbirth compared with white women. After stillbirth, women are subject to a sevenfold increased risk of post-traumatic stress compared with women after a live-birth. This paper presents findings from phase one of a National Institutes of Health funded, two-phase feasibility study to examine an online yoga intervention to reduce symptoms of post-traumatic stress in mothers after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The recent need for social distancing has driven many activities online, and yoga enjoys obvious logistical advantages over massage therapy in keeping with these measures. Pilot studies of online yoga programs have shown improvements in mental well-being in specialized populations, 122,123 and tele-yoga has been suggested as a specific means of stress management in the era of COVID-19. 124 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The recent need for social distancing has driven many activities online, and yoga enjoys obvious logistical advantages over massage therapy in keeping with these measures. Pilot studies of online yoga programs have shown improvements in mental well-being in specialized populations, 122,123 and tele-yoga has been suggested as a specific means of stress management in the era of COVID-19. 124 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention groups (LD and MD) were asked to follow a 12-week online yoga prescription developed by the research team [18]. Briefly, the prescription included 12 videos developed for women who had experienced stillbirth [18] and the remaining 48 videos were chosen using Udaya's existing library of more than 600 yoga videos. Udaya is an online streaming platform that provides yoga videos that vary in length, style, and language, instructed by experienced yoga teachers (e.g., 200 h or more of yoga training).…”
Section: Interventionmentioning
confidence: 99%
“…Second, the sample was not necessarily representative of the population of the women who have had stillbirths in the US, as most were white and higher income. Although in a previous study we asked minority women who had experienced stillbirth about cultural barriers to recruitment and about their perceptions and opinions on yoga [18], additional recruiting methods are needed for representative samples to ensure generalizability of the results. Third, this study had a high number of dropouts.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In addition, Black women are less likely to seek professional help for psychological distress symptoms in general due to a lack of compassionate care from health care professionals, 8,9 lack of Black health care providers, 10,11 and stigma surrounding mental health care within Black communities. 12,13 Instead, they tend to emphasize spiritual and religious practices, talking with a few close friends, and solitude. 5,14 Although both Black and White women agree social support is important for healing from a stillbirth, Black women tend to find other women most supportive, whereas White women often find the child's father most supportive.…”
Section: Introductionmentioning
confidence: 99%